The Response of Human Resources and Health Workers in the Surgical Operating Room Due to the COVID-19 Pandemic - Cipta Pramana; Kardoyo Kardoyo (Indian Journal of Forensic Medicine & Toxicology, 2021)
The COVID-19 pandemic that occurred around the world with infections that spread so fast has changed patterns of life, including social, economic, education, and health. The impact of the pandemic has changed the health system and requires new policies that can adapt to these conditions. K.R.M.T. WongsonegoroHospital, Semarang City, Indonesia, which is a referral hospital for Covid-19 patients, needs to prepare health infrastructure in COVID-19 services. We report the impact of the COVID-19 pandemic on surgical service activities and improving the quality of human resources, especially health workers in the Central Surgical Installation. The hospital is preparing a special operating room for COVID-19 patients so that it does not spread to health workers. There are 18 surgeons and 7 anesthetists. Assisted by 30 surgical nurses and 7 anesthetic nurses. Since the emergence of the COVID-19 case in Indonesia in March 2020, surgery is only carried out in emergency cases and has postponed elective surgery. So that there will be a 50% decrease in the number of surgical services in 2020 compared to 2019. Human resources involved in COVID-19 patient surgery activities must also be trained in knowledge in how to wear and remove Personal Protective Equipment, handling surgical linen and know the flow of patients into and out of the room surgery.